2021
DOI: 10.1093/europace/euab216
|View full text |Cite
|
Sign up to set email alerts
|

Personalized paroxysmal atrial fibrillation ablation by tailoring ablation index to the left atrial wall thickness: the ‘Ablate by-LAW’ single-centre study—a pilot study

Abstract: Aims To determine if adapting the ablation index (AI) to the left atrial wall thickness (LAWT), which is a determinant of lesion transmurality, is feasible, effective, and safe during paroxysmal atrial fibrillation (PAF) ablation. Methods and results Consecutive patients referred for PAF first ablation. Left atrial wall thickness three-dimensional maps were obtained from multidetector computed tomography and integrated into t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
46
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(49 citation statements)
references
References 21 publications
0
46
0
Order By: Relevance
“…12 Beyond the AI-guided approach including catheter-tip to tissue contact force, power and ablation duration patients with advanced AF may benefit from further personalized ablation strategies. Adapting the AI to the LA wall thickness may allow for even lower RF delivery, fluoroscopy, and procedure times while obtaining a high rate of AF-free survival as demonstrated by Teres et al 13 Compared to the AI-guided approach, temperature-guided AF ablation with the DT catheter was associated with a significantly longer mean procedure duration, significantly more RF applications, a significantly shorter total RF duration as well as significantly lower fluoroscopy doses. Prior studies using the DT catheter reported on even longer procedure duration (84-159 min), RF application-(18-21 min), and fluoroscopy times (9-13 min).…”
Section: Procedural Datamentioning
confidence: 99%
See 2 more Smart Citations
“…12 Beyond the AI-guided approach including catheter-tip to tissue contact force, power and ablation duration patients with advanced AF may benefit from further personalized ablation strategies. Adapting the AI to the LA wall thickness may allow for even lower RF delivery, fluoroscopy, and procedure times while obtaining a high rate of AF-free survival as demonstrated by Teres et al 13 Compared to the AI-guided approach, temperature-guided AF ablation with the DT catheter was associated with a significantly longer mean procedure duration, significantly more RF applications, a significantly shorter total RF duration as well as significantly lower fluoroscopy doses. Prior studies using the DT catheter reported on even longer procedure duration (84-159 min), RF application-(18-21 min), and fluoroscopy times (9-13 min).…”
Section: Procedural Datamentioning
confidence: 99%
“…[7][8][9][10] Initial studies have demonstrated the feasibility and safety of a combined, AI-guided HPSD ablation approach for AF ablation using a conventional force-sensing equipped ablation catheter. [11][12][13] Using a power-controlled 50 W HPSD setting, a high irrigation-flow rate is required to prevent charring and thrombus formation. Thus, real-time temperature monitoring at the catheter tip is limited.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Of note, a recent study showed that LAWT-tailored, individualized AI values might result in similarly good results, even with somewhat lower AI targets. On the other hand, this approach is time consuming, but does not seem to be better in efficacy or safety [43].…”
Section: Discussionmentioning
confidence: 99%
“…Catheter ablation was performed by the By-LAW method, 9 with patients under general anesthesia with high-frequency, low-volume ventilation. Oral anticoagulation was uninterrupted, and periprocedural anticoagulation was performed to achieve an activated clotting time >300 seconds.…”
Section: Methodsmentioning
confidence: 99%